Type on the Sound Absorption Coefficient Chicken Feather Composite - Artayani, Meldawati; Kusno, Asniawaty; Jamala, Nurul; Mulyadi, Rosady (ASTONJADRO, 2024)
the potential to be a composite reinforcement and increase sound absorption through the Chemical Pulping process. This study aims to investigate the alleged influence of the use of matrix type on the strength of sound absorption in chicken feather fiber composites. The research method used is experimental research with the manufacture of composite specimens that vary the volume fraction of composite fibers with various types of matrices. Sound absorption testing using impedance tubes. Data analysis techniques in this study use descriptive data analysis. The results of this test show the effect of using matrix type on increasing the absorption coefficient of SBA composites. The maximum absorption coefficient is found in the SBA-K composite (Chicken Feathers – Kanji).